Investigação da exposição nutricional as aflatoxinas em indivíduos adultos na região amazônica: um biomonitoramento dos níveis urinários de Aflatoxina M1 - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Nutritional exposure to aflatoxins is considered a health problem and a risk to food safety. Therefore, biomonitoring of aflatoxin M1 in biological fluids is useful to prevent the deleterious effects of this mycotoxin on the human body. In regions where the food base consists of foods potentially contaminated by aflatoxins, biomonitoring studies are extensive; however, in Amazonian environments, there is a need for clinical studies to assess the risk of exposure to aflatoxins, which justifies the performance of this study. The objective of the present study was to investigate the levels of nutritional exposure to aflatoxins in humans by determining urinary levels of aflatoxin M1 (AFM1) in a population from the city of Manaus/Amazonas. This was a cross-sectional study that analyzed 37 urine samples from individuals with and without comorbidities who consumed foods potentially contaminated by aflatoxin and regional foods. The study was conducted through a dietary survey and urinary AFM1 levels, confirmed by Competitive Enzyme-Linked Immunosorbent Assay (ELISA). In the study, 54.1% (n=20) of the samples were positive for the presence of AFM1 in urine. The median and interquartile range of concentration was 0.405 ng/ml (0.180 ng/ml and 6.835 ng/ml). The foods that had an association between consumption and positive urinary levels were corn cake (p<0.010) and tapioca gum (p<0.023). Individuals who used vitamins or supplements had a negative result for AFM1, compared to those who did not use them (p<0.036). We conclude that nutritional exposure to aflatoxins is an important factor even in regions with a low incidence of environmentally contaminated foods and new types of foods may be harmful if contaminated by these aflatoxins. Furthermore, micronutrients can be an important mechanism to minimize the deleterious effects of aflatoxins on the human body, preventing the toxic effects of these toxic agents in the long term.
Keywords: Aflatoxina; Segurança alimentar - Avaliação de riscos de saúde; CIENCIAS DA SAUDE; Aflatoxina M1; Biomonitoramento; Alimentos; Urina; Exposição nutricional